2016
DOI: 10.1021/acs.jafc.6b02035
|View full text |Cite
|
Sign up to set email alerts
|

Orbitide Composition of the Flax Core Collection (FCC)

Abstract: The flax (Linum usitatissimum L.) core collection (FCC) was regenerated in Saskatoon, Saskatchewan and Morden, Manitoba in 2009. Seed orbitide content and composition from successfully propagated plants of 391 accessions were analyzed using high-throughput analyses employing high-performance liquid chromatography (HPLC) with reverse-phase monolithic HPLC columns and diode array detection (HPLC-DAD). Seed from plants regenerated in Morden had comparatively higher orbitide content than those grown in Saskatoon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Hence, orbitide concentrations of 1 : 3 : 8 observed in ‘Hollandia’ and ‘Z 11637’ deviated from the 1:1:1 ratio expressed in ‘CDC Bethune’. These findings were consistent regardless of harvest location (Saskatoon, SK or Morden, MB) and year (2009, 2010, 2011) and corroborate observations made by Burnett et al [ 23 ] (Table 1 ). Low level detection of 1 and 3 in ‘Hollandia’ and ‘Z 11637’ resulted from flaxseed samples that were contaminated with one or more other accessions within the FCC.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Hence, orbitide concentrations of 1 : 3 : 8 observed in ‘Hollandia’ and ‘Z 11637’ deviated from the 1:1:1 ratio expressed in ‘CDC Bethune’. These findings were consistent regardless of harvest location (Saskatoon, SK or Morden, MB) and year (2009, 2010, 2011) and corroborate observations made by Burnett et al [ 23 ] (Table 1 ). Low level detection of 1 and 3 in ‘Hollandia’ and ‘Z 11637’ resulted from flaxseed samples that were contaminated with one or more other accessions within the FCC.…”
Section: Resultssupporting
confidence: 91%
“…2b ). Stefanowicz [ 26 ], Okinyo-Owiti et al [ 20 ], and Burnett et al [ 23 ] have reported similar observations for orbitide content of fresh flaxseed extracts. Unoxidized flaxseed extracts from ‘Hollandia’ and ‘Z 11637’ contained known orbitides 7 , 10 , 14 , and 15 as found in ‘CDC Bethune’.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations